Government spending: how to cut it - Mundle, Sudipto; Mukhopadhyay
The fiscal deficit which the government has adopted as a key indicator of its fiscal policy stance, is not a directly controlled instrument variable. But by setting the fiscal deficit and some other policy variables at desired levels, it is possible to project the inflation rate, real growth rate and Central Government expenditure level under alternative trade performance assumptions with the help of a computable macro-economic model. Author outlines some measures for expenditure compression which may be feasible in the immediate future as well. Apart from the short term gains, the major importance of the economy measures proposed in the article is their potential for containing Central Government expenditur
Keywords: Fiscal Policy; Expenditures, Government - India